CHILDHOOD OBESITY IN MACEDONIAN PRESCHOOL CHILDREN, PREVALENCE AND PREVENTION - Trpkovska, Biljana; Zafirova, Biljana; Zivadinovikj, Julija; Matveeva, Niki; Cadikovska, Elizabet; Bojadzieva, Biljana; Dodevski, Ace; Paunkoska, Anamarija (Journal of Morphological Sciences, 2022)
Assessment of sex-specific differences of anthropometric parameters as indicator of growth and nutritional status in preschool children from Macedonia.The study included a total of 200 healthy preschool children from Macedonian nationality. Thirthteen anthropometric parameters were measured, defining longitudinal, circular and transversal dimensionality of the skeleton using standard technique and instruments for measurement. The following indices were selected and calculated: weight-for –age; height-for-age and BMI. Skin –folds (triceps, scapula, thigh) were also measured. Qualitative examinations were with self-organizing maps. Sex-specific differences for almost all anthropometric parameters were detected, but they were not significant. Girls showed higher values than boys regarding height and weight, but there were no significant differences concerning BMI. Values at the 50 th percentile in girls were 20 kg for BW, 108.1 cm for BH and 16.82 kg/m² for BMI. The values of these parameters in boys were 19.75 kg for BW, 108.25 cm for BH and 16.24 for kg/m² for BMI. The values for triceps skin-fold were higher in boys than (13.0 ±3.0) than in girls (12.5 ±3.6).The results obtained can be used as criteria for assessment and detecting deviations in growth and nutritional status in preschool children. Keywords: anthropometry, growth, nutritional status, preschool children, self organizing maps.